The Responsiveness Of Board Of Trustees Hospitals According To The World Bank\'s Organizational Reform Model In Isfahan - Masoud Ferdosi; Amin Saberi Nia; Farzaneh Mahmoudi Meymand; Fatemeh Nezamdoust; Leila Shojaei (Tehran University of Medical Sciences, 2013)
Background and Aim: Transforming government hospitals into autonomous units improved hospitals. This study was performed to evaluate the responsiveness of board of trustees hospital according to the world bank's organizational reform model (Preker Model) in isfahan city. Materials and Methods: The study was a qualitative research method. In this research, depth and semi-structured interviews were carried out and purposive sampling was used. The study population were top managers of Amin and Alzahra hospitals . Sampling was started with the first participant until saturated level of information, participants completed the 8 cases. Results: According to interviews, the current role and contribution of non-university institutions (e.g. municipalities representatives) in hospital board of trustees is neither bold nor transparent. These hospitals can address minimum changes in their mechanisms of accountability after developing board of trustees. Conclusion : It is rational for hospitals as they undergo organizational reform and developing board of trustees, to have more rights for decision making. Further more, their accountability mechanism should change accordingly.